1993
DOI: 10.4319/lo.1993.38.4.0709
|View full text |Cite
|
Sign up to set email alerts
|

The stoichiometry of carbon, nitrogen, and phosphorus in particulate matter of lakes and oceans

Abstract: The mean carbon, nitrogen, and phosphorus contents of particulate material for 5 1 lakes or lake basins, extending from arctic to tropical climatic regions, including small lakes as well as the largest lakes in the world, indicate that Redfield ratios are the exception rather than the rule in freshwater. The C: P and N : P ratios are more variable for lake particles but generally higher than marine particles, and the mean molar C: N, C: P, and N : P ratios are substantially higher than the Redfield ratio of 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

28
349
4
11

Year Published

1997
1997
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 545 publications
(392 citation statements)
references
References 42 publications
28
349
4
11
Order By: Relevance
“…The C : P ratios (415-691; 396-660 adjusted for carbonate) and N : P ratios (26-72) in the present study (Fig. 8b, c), are within the commonly quoted ranges for phosphorus limitation of benthic marine microalgae (C : P > 180 and N : P > 22; Hillebrand and Sommer 1999), freshwater periphyton (C : P > 369 and N : P > 32; Kahlert 1998) and severe phosphorus limitation of phytoplankton (C : P > 258, N : P > 22) (Hecky et al 1993). Thus, the high C : P ratios (combined with high N : P ratios and low phosphorus contents) of L. majuscula in the present study strongly support phosphorus limitation of L. majuscula in Deception Bay.…”
Section: Tissue Nutrient Content and Changessupporting
confidence: 56%
See 2 more Smart Citations
“…The C : P ratios (415-691; 396-660 adjusted for carbonate) and N : P ratios (26-72) in the present study (Fig. 8b, c), are within the commonly quoted ranges for phosphorus limitation of benthic marine microalgae (C : P > 180 and N : P > 22; Hillebrand and Sommer 1999), freshwater periphyton (C : P > 369 and N : P > 32; Kahlert 1998) and severe phosphorus limitation of phytoplankton (C : P > 258, N : P > 22) (Hecky et al 1993). Thus, the high C : P ratios (combined with high N : P ratios and low phosphorus contents) of L. majuscula in the present study strongly support phosphorus limitation of L. majuscula in Deception Bay.…”
Section: Tissue Nutrient Content and Changessupporting
confidence: 56%
“…8b) in the current study are similar to ratios (46-51) reported from Deception Bay in 2005 but are higher than the ratio (14) reported for Deception Bay in 1999-2000 (Watkinson et al 2005) and the Eastern Banks (16.4-22.4) (Ahern et al 2007). The N : P ratios reported in the present study, particularly during the incipient, rapid growth and plateau phases (47-72), were substantially higher than the various optimum N : P ranges published in the literature, including optimum ratios for unicellular phytoplankton (16) (Redfield et al 1963), freshwater periphyton (18) (Hecky et al 1993), medium ratio (30) for benthic plants (Atkinson and Smith 1983) and the optimum range (13-22) for benthic microalgae (Hillebrand and Sommer 1999). The higher N : P ratios recorded in the present study are not unusual for nitrogen-fixing species, which have often been documented as having higher N : P stoichiometry than non-diazotrophic species (Table 4).…”
Section: Tissue Nutrient Content and Changescontrasting
confidence: 53%
See 1 more Smart Citation
“…Biomass stoichiometry is a useful tool for detecting nutrient limitation and has been widely applied to phytoplankton (Hecky et al, 1993). Recently, this concept has been transferred to benthic microalgae (Kahlert, 1998;Hillebrand & Sommer, 1999).…”
Section: Effect Of Nutrient Treatmentmentioning
confidence: 99%
“…These confusions are the result of ignoring the underlying concept used (e.g. Hecky et al 1993) or idealizing the circumstances that are constrained by critical assumptions (e.g. Andrews & Muller 1983).…”
Section: Abdelrhman 2005mentioning
confidence: 99%